Putting the Husband Through: The Role of Credit Constraints in the Timing of Marriage and Spousal Education - Iyigun, Murat; Lafortune, Jeanne (Journal of Labor Economics, 2023)
In the United States, age at first marriage was lowest and the education gap between husbands and wives was highest during the 1950s. The conventional explanation for such a negative correlation is that early marriage leads to earlier and higher fertility, which in turn prevents women from acquiring education. Here, we propose that early marriages enabled couples to overcome credit constraints in education. A model that includes this motive and mechanism can replicate not only the marriage and education patterns observed in the middle of the century in the United States but also the overall trends over the twentieth century.